Scrotal Skin Metastasis from Rectum Adenocarcinoma - Ozgen, Aytul (PAGEPress Publications, Pavia, Italy, 2013)
Cutaneous metastases of rectal adenocarcinoma is a rare phenomenon. We present a 65 year-old man with a painless nodule on the scrotal skin. Excisional biopsy of the nodules revealed a metastasis from rectum adenocarcinoma. Afterwards, the left scrotum was treated with a radiation therapy and the patient also received a salvage chemotherapy. The patient is still alive without any distant metastasis after the therapy, which was initiated 12 months ago.